INITIAL AND SUSTAINED RESPONSE EFFECTS OF 3 VAGAL MANEUVERS IN SUPRAVENTRICULAR TACHYCARDIA: A RANDOMIZED, CLINICAL TRIAL - DENİZBAŞI ALTINOK, ARZU; ÖZPOLAT, ÇİĞDEM; AKOĞLU, HALDUN; ONUR, ÖZGE ECMEL (ELSEVIER SCIENCE INC, 2019)
Background: For acute termination of supraventricular tachycardia (SVT), vagal maneuvers, including the standard Valsalva maneuver (sVM), modified Valsalva (mVM) maneuver, and carotid sinus massage (CSM), are first-line interventions. There is no criterion standard technique. Objective: This prospective, randomized study was aimed at analyzing the success rates of these 3 vagal maneuvers as measured by sustaining sinus rhythm at the fifth minute and SVT termination. Methods: We conducted this prospective, randomized controlled study in an emergency department (ED). We enrolled all the patients who were admitted to the ED and diagnosed with SVT. We randomly assigned them to 3 groups receiving sVM, mVM, and CSM and recorded the patients' responses to the vagal maneuvers and SVT recurrence after vagal maneuvers. Results: The study was completed with 98 patients. A total of 25 (25.5%) instances of SVT were initially treated successfully with vagal maneuvers. The success rate was 43.7% (14/32 cases) from mVM, 24.2% (8/33) for sVM, and 9.1 % (3/33) for CSM (p < 0.05). At the end of the fifth minute, only 12.2% (12/98) of all patients had sinus rhythm. Sinus rhythm persisted in 28.1% (9/32) of patients in the mVM group, 6.1% (2/33) of patients in the sVM group, and 3% (1/33) in the CSM group at the fifth minute (p < 0.05). Conclusion: mVM is superior to the CSM maneuver in terminating SVT and maintaining rhythm. We conclude that it is beneficial to use mVM, which is more effective and lacks side effects. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: carotid sinus massage; modified valsalva; standard valsalva; supraventricular tachycardia; vagal maneuver; VALSALVA MANEUVER; TERMINATION; STANDARD